Are stabilisation exercises effective after epidural steroid injection in patients with cervical radiculopathy? a prospective randomised controlled trial - Tayboğa, Umut İslam; Olgun, Yücel; Gündüz, Osman Hakan; Şencan, Savaş (My University, 2025)
Background: Cervical radiculopathy is caused by dysfunction of nerve roots in the cervical spine. While many studies have assessed the effectiveness of interlaminar epidural steroid injection (ILESI) and stabilisation exercises separately for this condition, our study aims to evaluate the impact of different stabilisation exercise programmes following ILESI on treatment outcomes in radiculopathy patients. Methods: Sixty-two patients with cervical radiculopathy were randomised into three groups: cervical ILESI-only (CO), neck stabilisation group (NSG) and scapular stabilisation group (SSG). The CO group received only ILESI, while NSG and SSG underwent stabilisation exercises following ILESI. Outcomes were assessed using the Numerical Rating Scale (NRS) for neck and arm pain, the Neck Disability Index (NDI) for functionality and the Short Form-12 (SF-12) for quality of life at baseline, 1 and 3 months posttreatment. Results: When NRS, NDI and SF-12 parameters were analysed in all groups, a statistically significant improvement was observed in the 1st and 3rd months compared to the pretreatment period. While the improvement in SF-12 physical parameters was significant in SSG and NSG in the 1st month compared to the pretreatment period, no significant difference was found in the CO group in the posttreatment periods. When the 1st and 3rd month results were analysed in NSG, a greater improvement was observed in terms of NRSNECK parameter in both evaluations compared to the other groups. Conclusions: Stabilisation exercise programme, especially neck stabilisation, should be included after ILESI treatment due to positive effects on treatment outcomes. Significance: To the best of our knowledge, our study is the first to investigate the effect of a stabilisation exercise programme after ILESI on treatment outcomes in patients with radiculopathy due to cervical disc herniation. It is a valuable study in terms of its prospective design, its specific and homogeneous patient population and its results. Our study will help clinicians when prescribing exercise programmes for these patients. Trial Registration: NCT05307211.
Keywords: Anesthesiology; Clinical Neurology; Neurosciences